Guardians of the Galaxy. Vol. 2, Grootrise - Kelly, Collin; Lanzing, Jackson (Marvel Worldwide, Inc., 2024)
The secrets of Grootfall revealed! One year ago, the Guardians were more than a team - they were the galaxy's heroes! But now they're outlaws - guns for hire roaming the frontier in the vain hope of stopping one of their own. How did the Guardians fall, and what changed Groot into the monster he's become? As Emperor Hulkling and Wiccan try to safeguard the Kree/Skrull Empire from the Grootfall, is this the beginning of a new Guardians of the Galaxy? Meanwhile, none have been changed more by this ordeal than Mantis. What fractured her, and what secrets has she been keeping from the team? It's time to deal with the past, and only one thing can help: an Infinity Stone! After the Grootfall, will there be a Grootrise?